Cholesteric fingersa review - Pirkl, Slavomír; Oswald, Patrick (Univerzita Pardubice, 2005)
The behaviour of a cholesteric liquid crystal subjected to a topological frustration together with an a.c. electric field is described. The frustration comes from the homeotropic anchoring of the molecules on the two electrodes limiting the sample. This geometrical boundary condition is incompatible with the helical structure of the phase. As a result, the helix can partly unwind to form "cholesteric fingers" (CF) of different types in coexistence with the homeotropic nematic phase.We review their static and dynamic properties in electric field.
Keywords: tekuté krystaly; struktura; dynamické vlastnosti; elektrické pole